2017
DOI: 10.1155/2017/2868143
|View full text |Cite
|
Sign up to set email alerts
|

Renaissance of Conventional First-Line Antibiotics inSalmonella entericaClinical Isolates: Assessment of MICs for Therapeutic Antimicrobials in Enteric Fever Cases from Nepal

Abstract: Enteric fever caused by Salmonella enterica is a life-threatening systemic illness of gastrointestinal tract especially in tropical countries. Antimicrobial therapy is generally indicated but resistance towards commonly used antibiotics has limited their therapeutic usefulness. Therefore, we aimed to determine the antimicrobial susceptibility pattern by minimum inhibitory concentration method of common therapeutic regimens against Salmonella enterica from enteric fever clinical cases. Salmonella enterica clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 32 publications
9
15
0
Order By: Relevance
“…However, we observed a very high level of FQs and nalidixic-acid resistance, but relatively low rates to conventional drugs. The findings are in line with recent epidemiological studies conducted in the Nepalese population(11)(13)(14) (16).The low rate of resistance to conventional drugs was observed, probably due to discontinuation in the therapeutic regimen for a longer time, high molecular weight self-transmissible plasmid inducing resistance could have lost or de novo susceptible strain might have emerged in these days (11) (22). Due to mutation in the genes coding for DNA gyrase (gyrA and gyrB) and topoisomerase IV (parC and parE), the high level of nalidixic-acid resistance occurs, in general (23).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, we observed a very high level of FQs and nalidixic-acid resistance, but relatively low rates to conventional drugs. The findings are in line with recent epidemiological studies conducted in the Nepalese population(11)(13)(14) (16).The low rate of resistance to conventional drugs was observed, probably due to discontinuation in the therapeutic regimen for a longer time, high molecular weight self-transmissible plasmid inducing resistance could have lost or de novo susceptible strain might have emerged in these days (11) (22). Due to mutation in the genes coding for DNA gyrase (gyrA and gyrB) and topoisomerase IV (parC and parE), the high level of nalidixic-acid resistance occurs, in general (23).…”
Section: Discussionsupporting
confidence: 89%
“…In our study, among tested antibiotics, low rate of azithromycin resistant strain was observed on MIC which is similar as Khanal et al reported such efficacy-lower MIC and resistance trend against the isolates, in his study (22). In the Nepalese population, treatment failure on azithromycin treatment is yet not reported; nevertheless, an increase in MIC was reported in the patients from other countries.…”
Section: Discussionsupporting
confidence: 89%
“…2 In our study, cotrimoxazole and chloramphenicol are 100% sensitive to all salmonella species, which is similar to the study done in 2002. 10 Similarly, in another study done by Khanal et al, 11 the conventional first line antibiotics, namely, co-trimoxazole and chloramphenicol showed 100% sensitivity to salmonella species. The quinolones group of drugs emerged as useful drugs in the 90s for the treatment of multiple drug resistant cases.…”
Section: Discussionmentioning
confidence: 88%
“…In Nepal, antibiotic resistance among Gram negative bacteria is increasing (Thapa et al, 2006) and screening of such resistance is routinely done using the disc diffusion (DD) method following CLSI standard guidelines. But this DD method has been claimed inadequate to determine to reduce susceptibility of fluoroquinolones by many studies (Gupta et al, 2020;Bhetwal et al, 2017;Khanal et al,2017) so NAR was used as a surrogate marker in those cases. Unfortunately, the fluoroquinolones resistance among Salmonella continued to increase in Nepal (Gupta et al, 2020;Pokharel et al, 2016;Karki et al, 2013) and to implement an appropriate treatment for enteric fever patients, an efficient screening method along with a standard CLSI guideline is utmost necessary (Bhetwal et al, 2017;Khanal et al,2017).…”
Section: Introductionmentioning
confidence: 99%